Distributional effects of FDI: How the interaction of FDI and economic policy affects poor households in Bolivia - Peter Nunnenkamp; Rainer Schweickert; Manfred Wiebelt (Kiel Institute for the World Economy (IfW), 2006)
This paper provides a computable general equilibrium analysis of the medium to long-run impact of FDI inflows on poverty and income distribution in Bolivia. The CGE analysis addresses several important transmission channels which have been neglected in the empirical literature by (i) investigating the impact of FDI inflows on incomes of urban and rural households; (ii) taking into account informal activities; and (iii) differentiating between various segments of the urban workforce, whereas previous studies are typically confined to the dichotomy between white-collar and blue-collar workers in manufacturing industries. The simulation results suggest that FDI inflows add to Bolivia's investment ratio, enhance economic growth, and reduce poverty. However, the income distribution typically becomes more unequal. In particular, FDI widens income disparities between urban and rural areas Our results point to two levers through which the Bolivian government may promote growth-enhancing and poverty-alleviating effects of FDI. First, it seems important to overcome labor market segmentation. Second, complementary public investment in infrastructure may help remove bottlenecks in the absorptive capacity of the economy that tend to limit productive employment of the poor. Yet, simulated policy reforms or alternative productivity scenarios are hardly effective in reducing the divide between urban and rural areas.
Keywords: D3; F21; C68; O5; 330; Poverty and income distribution; Bolivia; Computable general equilibrium analysis; Foreign direct investment; Direktinvestition; Wirtschaftspolitische Wirkungsanalyse; Armut; Einkommensverteilung; Stadt-Land-Beziehung; Allgemeines Gleichgewicht; Schätzung; Bolivien